Cdk Phosphorylation of a Nucleoporin Controls Localization of Active Genes through the Cell Cycle - Garvey Brickner, Donna (The American Society for Cell Biology, 2010)
Many inducible genes in yeast are targeted to the nuclear pore complex when active. We find that the peripheral localization of the INO1 and GAL1 genes is regulated through the cell cycle. Active INO1 and GAL1 localized at the nuclear periphery during G1, became nucleoplasmic during S-phase, and then returned to the nuclear periphery during G2/M. Loss of peripheral targeting followed the initiation of DNA replication and was lost in cells lacking a cyclin-dependent kinase (Cdk) inhibitor. Furthermore, the Cdk1 kinase and two Cdk phosphorylation sites in the nucleoporin Nup1 were required for peripheral targeting of INO1 and GAL1. Introduction of aspartic acid residues in place of either of these two sites in Nup1 bypassed the requirement for Cdk1 and resulted in targeting of INO1 and GAL1 to the nuclear periphery during S-phase. Thus, phosphorylation of a nuclear pore component by cyclin dependent kinase controls the localization of active genes to the nuclear periphery through the cell cycle.